The Effectiveness of Electronic and Print-Based Health Promotion on Emergency Prevention Behaviors for Respiratory Tract Infections: A Literature Review - Olandina da Silva Pereira; Erna Melastuti; Indah Sri Wahyuningsi; Dwi Heppy Rochmawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Respiratory tract infections remain a leading cause of global morbidity and mortality, making the enhancement of emergency prevention behaviors a critical focus of health promotion strategies. Electronic and print media are widely used for health education; however, their comparative effectiveness in influencing community behavior has not been comprehensively examined. This literature review aims to evaluate the effectiveness of electronic and print-based health promotion in improving emergency prevention behaviors related to respiratory tract infections. A systematic search was conducted in Scopus, ScienceDirect, PubMed, and Google Scholar for publications from 2020–2025, using the PICO framework and PRISMA guidelines. Search terms included the following keywords: Health Education, Electronic Media, Digital Media, Respiratory Infection, Acute Respiratory Infection, ARI, Emergency Prevention Behavior. The population included communities or families; the intervention comprised electronic media, the comparator was print media, and outcomes focused on emergency prevention behaviors related to acute respiratory infections. Of the 1,865 identified articles, 13 met the inclusion criteria and were analyzed, with 10 undergoing critical appraisal using the JBI Critical Appraisal Tools. Electronic media particularly educational videos, digital applications, and interactive messaging demonstrated greater effectiveness in improving knowledge, awareness, and rapid responses to danger signs. Print media remained beneficial for populations with limited access to technology and served as a reinforcement for educational messages. Both electronic and print-based health promotion strategies are effective; however, electronic media show superior influence on behavioral change.